2019
DOI: 10.1016/j.marpolbul.2019.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of anthropogenic pressures on Caspian Sea ecoregions

Abstract: Over the past decades, overall ecological conditions in the Caspian Sea have deteriorated. However, a comprehensive understanding of lake-wide spatial differences in anthropogenic pressures is lacking and the biological consequences of human impacts are poorly understood. This paper therefore aims at assessing the individual and combined effects of critical anthropogenic pressures on the Caspian Sea ecoregions. First, cumulative pressure scores were calculated with a cumulative environmental assessment (CEA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Several species of Pontocaspian molluscs are even thought to have gone extinct during the past century [5]. The causes for these declines are not well established, given the general lack of data for most species [5], but may be linked to anthropogenic activity [79]. However, the same causes could have been responsible for the apparent population increase, such as by reducing competition.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of Pontocaspian molluscs are even thought to have gone extinct during the past century [5]. The causes for these declines are not well established, given the general lack of data for most species [5], but may be linked to anthropogenic activity [79]. However, the same causes could have been responsible for the apparent population increase, such as by reducing competition.…”
Section: Discussionmentioning
confidence: 99%
“…Taghavi Motlagh (2001) reported that beluga is an overfished species in the Caspian Sea. During the past three decades, the anthropogenic invasive species, pollution and poaching influenced all components of the Caspian Sea (Pourang et al, 2016;Luttuada et al, 2019). Also, Beyraghdar Kashkooli et al (2017) reported that the environment of the Caspian Sea is shifted to a new condition.…”
Section: Introductionmentioning
confidence: 99%
“…The projected Caspian sea level decline combined with the loss of the highly productive and seasonally ice-covered northern Caspian shelf will severely affect this unique ecosystem, which is already under immense stress due to pollution, over-exploitation and the introduction of invasive species 10 . The reduction in winter sea-ice area will affect pupping grounds for the endangered Caspian seal 11 .…”
Section: Biodiversitymentioning
confidence: 99%